Analisis Kritis PHK dan Upaya Perlindungan Hak Pekerja dalam Kasus PT Far East Seating (Putusan No. 2/Pdt.Sus-PHI/2024/PN Smg) - Iqbal Tama Segara Hutabarat; Kevin Marihot Marpaung; Fakhri Fadhlurrohman Riyanto; Rayi Kharisma Rajib (JOURNAL SAINS STUDENT RESEARCH, 2025)
This study aims to examine legal protection for workers who have Fixed-Term Employment Agreements (PKWT) facing unilateral termination of employment (PHK), with an emphasis on its implementation in the case of PT Far East Seating Indonesia as stated in Decision Number 2/Pdt.Sus-PHI/2024/PN Smg. This study applies a normative legal approach, examining labor laws and court decisions as sources of positive law. Although labor laws, including Law Number 11 of 2020 concerning Job Creation and Government Regulation Number 35 of 2021, have stipulated the obligation to provide compensation for PKWT workers who are dismissed before their contract expires, existing practices often show violations of these provisions. The findings in the PT Far East Seating case show a discrepancy between the compensation provided and the applicable legal regulations, reflecting a lack of supervision and inconsistency in law enforcement. This study states that protection for contract workers in Indonesia is still normative and has not been fully implemented in the field, thus requiring the strengthening of supervisory tools and dispute resolution mechanisms that are more efficient and prioritize industrial justice.